Correction to: Ophiostomatoid fungi associated with Ips subelongatus, including eight new species from northeastern China - Zheng Wang; Ya Liu; Huimin Wang; Xianjing Meng; Xuewei Liu; Cony Decock; Xingyao Zhang; Quan Lu (IMA Fungus)
Following publication of the original article [1], the authors reported that Table 1 contained some errors in the GenBank number of BT gene. The correct Table 1 is presented below.